1969
DOI: 10.1002/pssb.19690330235
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Sublattices Magnetisations in Mn0.6Zn0.4Fe2O4 by Neutron Diffractometry and Mössbauer Spectrometry

Abstract: The temperature dependence of the two sublattices magnetisations of Mn,,,Zn,,,Fe,O, was determined in order to study the superexchange interactions in Mn2+-02+-Fe3+ linkages. The tetrahedral and octahedradl sublattices magnetisations were obtained in absolute scale by neutron diffractometry. Moreover by Mossbauer spectrometry the octahedral sublattice magnetisation was determined in a relative scale as il function of temperature. The results obtained by both methods show the same temperature dependences within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The total magnetic moment for a unit chemical formula is roughly 2 μ B , which is almost the same as the value estimated from the bulk magnetization at room temperature (see details in the supplementary section). We can confirm that the microscopic magnetic states in the standby state agree with the previously reported results for bare Mn–Zn ferrites that have not yet been assembled in an inductor device 20 23 . In the subsequent section, we will consider how the ferrite core becomes microscopically magnetized when an exciting current is supplied to the copper wires.…”
Section: Resultssupporting
confidence: 91%
“…The total magnetic moment for a unit chemical formula is roughly 2 μ B , which is almost the same as the value estimated from the bulk magnetization at room temperature (see details in the supplementary section). We can confirm that the microscopic magnetic states in the standby state agree with the previously reported results for bare Mn–Zn ferrites that have not yet been assembled in an inductor device 20 23 . In the subsequent section, we will consider how the ferrite core becomes microscopically magnetized when an exciting current is supplied to the copper wires.…”
Section: Resultssupporting
confidence: 91%
“…It is also known that MnZ+ ions show a strong preference for the A-sites. Mossbauer spectroscopic and neutron diffraction studies [20,21] have shown that Mn ions do not occupy the B-sites in the mixed ferrites MnxZn,-xFe,O,, for X 2 0.4. The ferrite sample Mn,.,Zn,,,Fe,O, used in this study has therefore the normal spinel structure: A-sites are occupied by Mn2+ and Znzt, whereas Fe3+ ions fill the B-sites only.…”
Section: Resultsmentioning
confidence: 99%
“…Konig et al 266 reported Mossbauer spectra on Zno.4Mno.6Fe204 at a number of different temperatures and suggested that the lineshape at, e.g., 300 K indicates a relaxational behavior. They ascribe this feature to the presence of Zn species which weaken the magnetic exchange interactions to such an extent that the frequency of the spin fluctuations becomes of the same order of magnitude as the rate of the nuclear Larmor precession.…”
Section: Relaxation Effectsmentioning
confidence: 99%